2009
DOI: 10.1097/pec.0b013e3181a792a9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Score for Predicting Hospitalization in Children With Influenza Virus Infection

Abstract: The presence of a high-risk medical condition, respiratory distress on physical examination, radiographic evidence of focal pneumonia, and influenza B infection were the 4 strongest predictors of hospitalization. The risk score assigned to a child with influenza may provide a disposition tool for predicting hospitalization in children in seasonal influenza epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Our findings are also consistent with CDC alerts on emergency warning signs of pandemic (H1N1) 2009 influenza ( 8 ) and a recent report by Echevarría-Zuno et al ( 9 ) from Mexico in which dyspnea, tachypnea, and cyanosis were prognostic factors for admission and death. Although the presence of any 1 underlying high-risk medical condition has been previously described as a risk factor for complication with seasonal influenza including hospitalization ( 10 ), a higher number of high-risk medical conditions is a stronger predictor of hospitalization (median number 2 vs. 0; p = 0.01).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings are also consistent with CDC alerts on emergency warning signs of pandemic (H1N1) 2009 influenza ( 8 ) and a recent report by Echevarría-Zuno et al ( 9 ) from Mexico in which dyspnea, tachypnea, and cyanosis were prognostic factors for admission and death. Although the presence of any 1 underlying high-risk medical condition has been previously described as a risk factor for complication with seasonal influenza including hospitalization ( 10 ), a higher number of high-risk medical conditions is a stronger predictor of hospitalization (median number 2 vs. 0; p = 0.01).…”
Section: Discussionmentioning
confidence: 95%
“…Although excellent clinical prediction rules for hospitalization of patients with community-acquired pneumonia are available (e.g., CURB-65 or pneumonia severity index), few data exist for influenza admissions ( 10 , 11 ). We propose a simple clinical guide for hospitalization of patients with pandemic (H1N1) 2009 infection by using results of our multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A few small cohort studies reported the proportion of children presenting at the emergency room in France21 and in USA,22 and the proportion of health care visits in the USA,6,23 caused by influenza B and A(H3N2). Influenza B-associated hospitalization rates in our study during 2011–2012 were more than twice the rates associated with A(H3N2).…”
Section: Discussionmentioning
confidence: 99%
“…The potential for bias is further compounded by age effects, which may impact both the likelihood of detection in surveillance systems and the probability of severe disease from infection. For example, while the majority of seasonal influenza A hospitalizations and deaths usually occur in the elderly, [4,5], evidence suggests that children are more likely to be infected [54], develop complications [55] and be hospitalized [56] for influenza B disease.…”
Section: Measuring Burden Of Diseasementioning
confidence: 99%